Judgment prey - Sandford, John, 1944 February 23- (New York : G.P. Putnam's Sons, 2023)
"Alex Sand was spending the evening at home playing basketball with his two young sons when all three were shot in cold blood. A wealthy federal judge, there's no short list of people who could have a vendetta against Sands, but the gruesome murders, especially that of his children, turn their St. Paul community on its head. Sand was on the verge of a major donation to a local housing charity, Heart/Twin Cities, and with the money in limbo, eyes suddenly turn to his grieving widow, Margaret Cooper, to see what she might do with the money."--
Keywords: Davenport, Lucas -- (Fictitious character) -- Fiction; Flowers, Virgil -- (Fictitious character) -- Fiction; Judges -- Crimes against -- Fiction; Widows -- Fiction; Murder -- Investigation -- Fiction; Detective and mystery fiction; Thrillers (Fiction)